Venezuela : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in Venezuela during 1995-97. The overall public sector balance shifted from a deficit of 7 percent of GDP in 1995 to a surplus of 7u percent of GDP in 1996. This massive swing was owing to a major increase in the underlying oil surplus, a decline in the non-oil underlying deficit, and the fact that virtually no financial assistance was provided to the banking system, compared with the cumulative 16 1\2 percent of GDP provided in 1994-95 in the context of the banking crisis.